2022
DOI: 10.1016/j.ipej.2022.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability as a marker of cardiovascular dysautonomia in post-COVID-19 syndrome using artificial intelligence

Abstract: Introduction Cardiovascular dysautonomia comprising postural orthostatic tachycardia syndrome (POTS) and orthostatic hypotension (OH) is one of the presentations in COVID-19 recovered subjects. We aim to determine the prevalence of cardiovascular dysautonomia in post COVID-19 patients and to evaluate an Artificial Intelligence (AI) model to identify time domain heart rate variability (HRV) measures most suitable for short term ECG in these subjects. Methods This observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 32 publications
2
50
3
Order By: Relevance
“…From a cardiovascular point of view, recent papers have highlighted an association between orthostatic intolerance (OI), including orthostatic hypotension (OH) and postural orthostatic tachycardia syndrome (POTS), with long COVID ( 17 19 ). OH is defined by a systolic or diastolic blood pressure decrease of 20 mmHg or 10 mHg, respectively, within 3 min of standing and it is the most common autonomic manifestation of long COVID ( 18 , 20 , 21 ). Studies suggest the prevalence of OH with long COVID may range between 10% ( 17 ) up to 41% ( 20 , 21 ).…”
Section: “Post-covid-19 Tachycardia Syndrome”mentioning
confidence: 99%
See 1 more Smart Citation
“…From a cardiovascular point of view, recent papers have highlighted an association between orthostatic intolerance (OI), including orthostatic hypotension (OH) and postural orthostatic tachycardia syndrome (POTS), with long COVID ( 17 19 ). OH is defined by a systolic or diastolic blood pressure decrease of 20 mmHg or 10 mHg, respectively, within 3 min of standing and it is the most common autonomic manifestation of long COVID ( 18 , 20 , 21 ). Studies suggest the prevalence of OH with long COVID may range between 10% ( 17 ) up to 41% ( 20 , 21 ).…”
Section: “Post-covid-19 Tachycardia Syndrome”mentioning
confidence: 99%
“…OH is defined by a systolic or diastolic blood pressure decrease of 20 mmHg or 10 mHg, respectively, within 3 min of standing and it is the most common autonomic manifestation of long COVID ( 18 , 20 , 21 ). Studies suggest the prevalence of OH with long COVID may range between 10% ( 17 ) up to 41% ( 20 , 21 ). Furthermore, tachycardia has been found to be a common symptom associated with long COVID, with 25–50% of patients in a tertiary post-COVID multidisciplinary team clinic reporting persistent tachycardia or palpitations ( 22 ).…”
Section: “Post-covid-19 Tachycardia Syndrome”mentioning
confidence: 99%
“… 21 Recently, ECG based AI model has also found its application in heart rate variability (HRV) monitoring among COVID-19 recovered patients. 22 Furthermore, AI finds a greater deal of application in smart wearable devices such as Apple smartwatch for routine ECG monitoring and arrhythmia detection in the general population. 23 …”
Section: Ai In Electrocardiographymentioning
confidence: 99%
“…HRV is the measurement of the variability of these N–N intervals. Some recent studies have indicated change in heart rate variability (HRV) in COVID-recovered subjects [ [28] , [29] , [30] ]. This indicates that tracking of the heart status of post-COVID recovered subjects can help in providing timely assistance to these subjects for better survival.…”
Section: Introductionmentioning
confidence: 99%